Correlation of body mass index and abnormal uterine bleeding in premenopausal women - Akalyaa, Kumarasamy; Shakuntala, Pattacheravanda Nanaiah; Renuka, Ramaiah (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: As the rate of obesity is increasing in women in the recent years, the incidence of endometrial cancer increases as the body mass index (BMI) increases. Despite the clear evidence linking endometrial cancer and obesity, there is limited public awareness of this relationship. This study was undertaken to evaluate the association of BMI and endometrial pathology in premenopausal women with abnormal uterine bleeding (AUB). Methods: An analytical case control study was conducted in 100 women between the age group of 40 to 55, with AUB in the Department of Obstetrics and Gynecology, ESIC-PGIMSR Bangalore between January 2018 and June 2019. The menstrual patterns and endometrial pattern by histopathology were analysed in women with BMI of 18.5 to 24.99 and ≥25. Results: The mean age of women participated in the study group of between 40- 55 years was 44.83. The mean duration of symptoms was 10.18 months in the cases group and 8.52 months in the control group. The menstrual patterns were comparable and there was no significant difference in both the groups. The mean endometrial thickness, mean BMI, hyperplasia with or without atypia were all higher in the cases group. The frequency of occurrence of atypical endometrial hyperplasia was higher in women with increasing BMI. Conclusions: We found increased BMI to be an important independent risk factor for the development of endometrial hyperplasia with atypia which is a precursor to endometrial carcinoma in premenopausal women with AUB.